Performance Analysis of Protection System on A 20 KV Distribution System Network at PT PLN Tutorial Shop Pematang Siantar City - Wanhar Afandi (Journal of Science Technology (JoSTec), 2021)
On era of globalization needs of electrical energy very high . In distribution of electrical energy expected could walk with good without existence interference. Distribution of electrical energy from generator until distribution to consumer expected could walk with good . In another side also often occur disturbance specifically on the distribution system power electricity . System distribution power electricity that uses cable air or cable soil often experience various interference . Frequent disturbances _ occur is disturbance symmetry or disturbance not the symmetry that can in the form of connection short one phase to land , between phase or break up wrong one or more . For knowing big current disturbance the required analysis system distribution transformer for knowing disturbances that will happen . Security setting design on network proper distribution is something effort protect equipment, system as well as needs consumer from possible disturbance occur in system distribution. Calculation current disturbance and big transformer nominal current will used as reference important in determination of transformer settings in deployment voltage to consumers